Magnetic properties of the antiferromagnetic site-disordered vanadate Zn2FeV3O11 - V. Likodimos; Guskos, N.; Glenis, S.; Szymczak, R.; Bezkrovnyi, A.; Wabia, M.; Typek, J.; Gasiorek, G.; Kurzawa, M.; Rychlowska-Himmel, I.; Blonska-Tabero, A. (European Physical Journal B, 2004)
The magnetic properties of the Zr2FeV3O11 vanadate, characterized by a disordered distribution of diamagnetic Zn 2+ and high-spin Fe3+ ions, are studied using magnetization and electron paramagnetic resonance (EPR) measurements. The dc susceptibility reveals antiferromagnetic interactions between Fe3 +spins with a Curie-Weiss temperature Θ = -58(1) K, followed by a transition to a frozen, spin-glass-like state at low temperature T f ≈ 2.55 K, indicating an inhomogeneous magnetic ground state. The temperature variation of the EPR parameters confirms the antiferromagnetic coupling of Fe3+ spins at high temperatures, while a distinct divergence is observed at T ≈ 55 K. This behavior is attributed to the inherent magnetic inhomogeneity of the system due to antiferromagnetic spin clusters.